Perancangan Aplikasi Seminarku dengan Pendekatan Design Thinking - Antonio Pangestu, Amora; Nealsen; Shelvian (Journal of Digital Ecosystem for Natural Sustainability, 2021)
During the COVID-19 pandemic, there have been many changes in activities that people usually do physically and have to adapt to technology. One of them is seminar activities that hold physical and mass meetings that must adapt to become webinars. Webinars have been attended by many students to seek the knowledge/information they need and can get e-certificates as a form of proof that they have participated in the webinar. However, many students who attend webinars just get an e-certificate, not the webinar topic they want to listen to. The Design Thinking approach is an approach that focuses on "Human-Centered Design" with 5 stages, namely empathize, define, ideate, prototype, test and implement. The results of this study produce a prototype application called Seminarku which will be used by students in facilitating the desired webinar activity.